2021
DOI: 10.3389/fimmu.2021.725989
|View full text |Cite
|
Sign up to set email alerts
|

A Peripheral Immune Signature of Labor Induction

Abstract: Approximately 1 in 4 pregnant women in the United States undergo labor induction. The onset and establishment of labor, particularly induced labor, is a complex and dynamic process influenced by multiple endocrine, inflammatory, and mechanical factors as well as obstetric and pharmacological interventions. The duration from labor induction to the onset of active labor remains unpredictable. Moreover, prolonged labor is associated with severe complications for the mother and her offspring, most importantly chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…49 The immune profiles of peripheral blood samples collected between induction and active labor paired with mass cytometry and computational algorithms identified maternal immune signatures able to predict time since labor induction. 49 Active labor is characterized by signs of heightened inflammation in maternal circulation, including STAT3 signaling in classical monocytes. 49 Ultimately, trajectories of these models over time revealed that delays in STAT3 and STAT5 signaling pathways are associated with subsequent labor complications.…”
Section: The Immunolog Ic Al Clock Of Preg Nan C Ymentioning
confidence: 99%
See 2 more Smart Citations
“…49 The immune profiles of peripheral blood samples collected between induction and active labor paired with mass cytometry and computational algorithms identified maternal immune signatures able to predict time since labor induction. 49 Active labor is characterized by signs of heightened inflammation in maternal circulation, including STAT3 signaling in classical monocytes. 49 Ultimately, trajectories of these models over time revealed that delays in STAT3 and STAT5 signaling pathways are associated with subsequent labor complications.…”
Section: The Immunolog Ic Al Clock Of Preg Nan C Ymentioning
confidence: 99%
“…49 Active labor is characterized by signs of heightened inflammation in maternal circulation, including STAT3 signaling in classical monocytes. 49 Ultimately, trajectories of these models over time revealed that delays in STAT3 and STAT5 signaling pathways are associated with subsequent labor complications. STAT3 signals the support of cell migration to fetal membranes during labor by interfering with the responsiveness of progesterone.…”
Section: The Immunolog Ic Al Clock Of Preg Nan C Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focused on the maternal monocyte and neutrophil responses to endotoxin, given that these are the primary cellular components of the peripheral blood. Yet, given the proposed involvement of systemic adaptive cellular immunity throughout pregnancy [ 79 82 ], future studies should evaluate how peripheral T-cell and B-cell responses differ between pregnant and non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there are likely to be many causative pathways that lead to one final common pathway for preterm parturition as a result of racism. Interestingly, although normal parturition involves inflammation, it is highly programmed with a transition point a little less than one month before the onset of labor, characterized by a shift in gene expression and cell signaling from a disposition of tolerance to one of rejection -labor [13,14]. This biochemical shift is evidence of a transcriptomic or immune clock of pregnancy that can be strained or dysregulated by physical or psychological stressors [11,27,28,29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%